Contractive adjustment in Mexico, 1982-1989 - LÓPEZ, G. J. (PSL Quarterly Review, 2013)
The work assesses the macroeconomic effects of the IMF’s contractive adjustment strategy in Mexico’s recent evolution, while raising some theoretical challenges to several of the underlying assumptions that have sustained the Mexican government’s recent economic policies. An overview of the strategy and of Mexico’s main economic policy measures is provided, and the evolution of effective demand is dealt with. The effects of contractive adjustment on Mexico’s growth performance are then appraised followed by a general discussion of the problems related to this strategy. JEL: E62